Study of oxidative stress and antioxidant status in male and female poisoning cases - A case control study - Gupta, Preeti; Desai , Prakash B (Journal of Indian Academy of Forensic Medicine, 2019)
Pesticide poisoning is the major health problem in the developing countries. For a person who is frustrated or stressed, and one who  wants to get rid of his problems, poison may seem to be the best answer. The stress and strain contribute to the imbalance between  antioxidant and oxidant status, which lead to various other disorders. A pilot study was conducted on patients admitted with  organophosphorus poisoning to our trauma and emergency care unit from January 2010 to March 2010. The various aspects of  treatment, complications, drug options and uncommon problems were evaluated. The levels of Vitamin C, E, Malondialdehyde and  activity of superoxide dismutase were measured in the participants of the study. Female subjects with organophosphorus poisoning  had significantly decreased levels of vitamin C, E and SOD and increased levels of MDA, when compared to male subjects with  organophosphorus poisoning and healthy controls.
Keywords: Oxidative stress; Organophosphorus poisoning; Pesticides